Conselhos tutelares: variáveis-chave e bom funcionamento: a interferência do perfil dos conselheiros, do desenho institucional e da articulação da política municipal da criança e do adolescente - Lafer, Inês Mindlin (2010)
Based on a qualitative research project conducted with agents of the Sistema de Garantia de Direitos [governmental system for assurance of citizenship rights], the present study identifies the elements that characterize a Conselho Tutelar (CT) [legal tutelar council at the municipal level] that “functions well”, and the relation between this performance and three variables: the councilors’ profiles, the institutional design; and the degree of articulation regarding the municipal policy devoted to children's and adolescents’ rights. The collected data allow us to conclude that these variables indeed influence the quality of work developed by the CTs.